Role of neuropilin-1 in CD8+ T cells - Barnkob, M (2018)
A major limiting factor in anti-tumour immunity is the ability of T cells to infiltrate and function in the suppressive tumour microenvironment. Semaphorins are a family of secreted and membrane-bound proteins that act as guidance cues in neurons and endothelial cells during development. By multimerizing heterodimers of neuropilin-1 (NRP1):plexin A receptors semaphorins strongly affect the F-actin cytoskeleton. Since many developmental programs are up-regulated in cancer cells, we hypothesized that tumours would hijack this physiological process to hamper immune responses. In tumour-specific T cells, we found that NRP1 was up-regulated in vitro and in vivo upon activation. To directly interrogate the role of Semaphorin 3A (Sema3A) in modulating T cell functions, we performed two complementary lines of research: 1. In vivo, we evaluated the role of NRP1 in T cell—tumour immunity by generating a T cell conditional knockout of NRP1 2. In vitro, we assessed the ability of Sema3A to modulate T cell survival, migration, adhesion and immunological synapse formation. We demonstrated that mice lacking expression of NRP1 on T cells control the growth of transplantable tumours cell-lines. We showed that addition of Sema3A affects T cell migration and adhesion. Additionally, we showed an inhibitory effect of Sema3A on peptide MHC:TCR synapse formation. Experiments suggested that these effects were mediated through Myosin IIA hyper-activation. Finally, we extended these findings to humans, demonstrating that in renal cell cancer a subset of tumour-infiltrating T cells express NRP1. These T cells are most likely newly activated T cells, in the sense that they were more clonal and expressed T cell antigen receptors (TCRs) specific for cancer testis (CT)-antigens. They were also found in close proximity to Sema3Arich areas. Taken together, our results provide novel insights into the NRP1/Plexin/Sema3A axis as an important tumour evasion mechanism.